" توصيف وتقييم الطرز المحلية للتفاح المنتشرة في موقعي كسب والربوة " - ديب علي; خربوتلي رشيد; البر كلود (Latakia University Journal -Biological Sciences Series, 2014)
أجريت هذه الدراسة عام 2013 في موقعي كسب والربوة التابعين لمحافظة اللاذقية حيث نفذت جولات حقلية بهدف حصر وتوصيف الطرز المحلية للتفاح المنتشرة في هذين الموقعين. تم من خلالها تحديد خمسة طرز محلية للتفاح هي: بربوري وسكري وشرخوشي وملكي وجبق جيان، وبنتيجة تحليل التباين عند المستوى /5%/ للصفات الظاهرية المدروسة والبالغة (17) صفة للورقة والزهرة والثمرة والبذرة . أظهرت هذه الطرز اختلافات شكلية واضحة فيما بينها ، إضافة إلى اختلافات معنوية من حيث محتواها من السكريات الكلية والحموضة الكلية ونسبة المواد الصلبة الذائبة الكلية ونسبة فيتامين C، ومن خلال حساب درجة التشابه ما بين هذه الطرز فقد وجدت أعلى درجة تشابه بين الطرازين شرخوشي وجبق جيان(41.17)%، وأقلها بين ملكي و سكري و بين سكري و جبق جيان(5.88)%. This study was conducted in 2013 in Kassab and Alraboa locations that is located in the province of Latakia, where carried out with the aim of rounds field inventory and characterization of types of local apples deployed in this locations. Was to determine which of five local types for apples are: Brobory and Sokary and Cherkhoshy and Malaky and JbakJian, and the outcome of the analysis of variance at the level / 5% / virtual studied for recipes of (17) characters for the leaves, blossoms, fruit and seed. These types showed clear differences formality between each other, in addition to the significant differences in terms of the content of total sugar, acidity, total soluble solids and the percentage of vitamin C, by calculating the degree of similarity between these types have found a higher degree of similarity was between the types Cherkhoshy and Jbak Jian(41.17)% , and the least was between Malaky and Sokary and between Sokary and Jbak Jian(5.88)% .